Optimization Of Carica Fruit Jelly Candy Formula: Study Of Proportions Of Carica Fruit Pure And Bovine Gelatin - Astuti, Santi Dwi; Ayuningtyas, Laksmi Putri; Dewi, Ervina Mela; Rachmadhani, Syafa Athala (Indonesian Journal of Food Technology, 2024)
Carica is one of the fruits that can be found in the Dieng Plateau, Wonosobo Regency. Carica fruit has a unique taste, distinctive aroma and chewy flesh. It has a sour, bitter and gum taste which can cause itching, so this fruit is only good for consumption if it has been processed first. One example is by processing it into jelly candy. This study aims to: (1) determine the proportions of puree carica and gelatine to produce carica jelly candy products that have a response of elasticity, cohesiveness, carica taste, softness, and maximum preference, yellow color in range, and minimum stickiness; (2) knowing the sensory characteristics of the jelly candy product with the formula recommended by the Design Expert program; (3) determination of the price of rubber between the optimum formula jelly candy product and the control. This study used the RSM (Response Surface Methodology) method with a CCD (Central Composite Design) experimental design consisting of 2 factors and 2 blocks to obtain 14 treatment combinations. The data obtained were analyzed using Design Expert software V.10 and SPSS IBM Statistics V.25 using a 95% T-test. The results of this study were the optimum carica fruit jelly candy formula with the proportion of carica fruit puree 28.85% and gelatine 12.75% with a desirability value of 0.75. Increasing the proportion of pure carica fruit causes an increase in the intensity of carica taste and yellow color. While the addition of gelatin gave an increase in the elasticity, cohesiveness, stickiness and level of preference of the panelists. The results of chemical tests on carica fruit jelly candy with optimum formula and control were the optimum product had higher moisture content, ash content, protein content, and vitamin C than the control product.